The role of catalyst metals to the growth of SI nanowire - Wahab, Yussof; Hamidinezhad, Habib (Faculty of Science, Universiti Teknologi Malaysia, 2009)
The metal catalyst plays an important role on the catalytic growth. The growth mechanism of silicon nanowires synthesized with several metal catalysts via chemical-vapordeposition (CVD) is discussed by using vapor–liquid–solid (VLS) mechanism. However, the growth of silicon nanowires is chiefly affected by the compound decomposition, gas stream, and temperature difference. Silicon nanowires were fabricated on single crystalline silicon wafer. VLS growth of needle-like silicon nanocones via atmospheric pressure chemical vapor deposition from SiCl4 and using Ga, Al, Pt, Au, and Pb catalysts are reported. Scanning electron microscopy and transmission electron microscopy reveal different shapes due to differences of metals catalyst. For all of catalysts the nanocones are composed of an oxide shell with a Si core. In this growth mechanism, the gradual etching of the Ga, Al catalyst leads to a gradual decrease of the catalyst volume, and hence the tapered Si nanowire morphology. The growth rates were higher with Pt than with Au under all processing conditions. Also the rate determining step is the incorporation of Si atoms in the lattice at the liquid/solid interfaces and, furthermore, the metal catalysts affect this step, resulting in different activation energy. Using Pb resulting the flower-like SiO2 nanostructures were formed. Unlike any previously observed results using Ga, Al, Pt, and Au as catalyst, the molten Pb-catalyzed VLS growth exhibits many amazing growth phenomena. The silicon oxide nanowires grow out perpendicularly from the surface of the metal Pb balls. For each ball, numerous nanowires simultaneously nucleate, grow at nearly the same rate and direction, and simultaneously stop growing. Hence the type of metals play an important role to the shape of Si nanowire formed.